Universal Health Coverage (UHC) - Samlee Plianbangchang (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The WHO Health for All goal of the year 2000 was unreachable due to a number of irreconcilable factors. However, governments agree that a resolution must be found to effectively cope with increasing health care costs. Furthermore, national health insurance schemes must be properly refined to suit local situations. Workable health policies and strategies for caring and treating sick people through reduced or cost effective methods must be developed as part of a Universal Health Coverage scheme. A review of progress made toward achieving the WHO goal of health for all. The purpose of this paper is to explore the government's role and responsibilities to educate and support society to achieve optimum health. Design/methodology/approach - This is a commentary piece. Findings - Participation and involvement of all people of all walks of life in the development and management of their nation's health care programs is an important requisite of good health for all. This should include financial participation and co-payment into the national health insurance scheme. Furthermore, national health care systems should involve or include the traditional/local and alternative systems of medicine in the most appropriate manner. Health care has to encompass the total range of comprehensive health interventions, inclusive of at least preventive, curative and rehabilitative care. Originality/value - This paper provides a review of the current health system constraints and assesses the effectiveness of available options by way of ensuring that a country-specific UHC system may be successfully implemented.